Обоснование конструкции и методики расчёта конструктивно-технологических параметров эжекционного аппарата, применяемого при пожаротушении - Дадашов, Ильгар Фарид; Ковалёв, Александр Александрович (НТУ "ХПИ", 2017)
Определены тактико-технические требования и предложена конструкция эжекционного аппарата для подачи гранулированного пеностекла для использования в технологии тушении горячих резервуаров хранения легковоспламеняющихся горючих жидкостей с использованием гелеобразующих огнетушащих и огнезащитных составов. Основываясь на известных методиках расчета конструктивных параметров струйных аппаратов, проведён теоретический анализ работы эжекционного аппарата для подачи гранулированного пеностекла предложенной конструкции, а также и предложена методика расчета его конструктивно-технологических параметров, что позволило создать опытно-экспериментальный образец.

The problem of extinguishing flammable combustible liquids is one of the most complicated in firefighting these fires cause significant economic and environmental damage and often lead to human casualties. Analysis showed the existing means and methods for extinguishing fires data provide a reasonably good result only for relatively small-size tanks of flammable liquids, combustibles. To extinguish fires data, we previously proposed to use gel-forming fire extinguishing and fire retardant compositions, which represent a binary system consisting of two separately stored and separately - simultaneously supplied formulations. To solve the problem of positive buoyancy layers of gelled compositions, it proposed to use granular foamed glass - non-flammable, non-volatile material, and as a device for supplying the granular foam glass we proposed to use an air ejection apparatus, the supply of foam glass granules via hose lines to the burning surface. The article defines the tactical and technical requirements and the proposed construction of an ejection apparatus for supplying granulated foamed glass. Based on the known methods for calculating the design parameters of jet devices, carried out a theoretical analysis of the ejection apparatus for supplying granulated foamed glass of the proposed design, as well as the design procedure of its structural and technological parameters, thereby creating Experimental sample for laboratory experimental research.
Substantiation of the design and methodology for calculating the design and technological parameters of the ejection apparatus used in fire extinguishing
Keywords: производительность; механизм шнековый; расход; мощность; performance; engineering design; auger mechanism; consumption; power